Senyawa Isoflavonoid dari Akar Gitaan (Willughbeia coriacea Wall.) - Aprenesya, Jamarlia; Ardiningsih, Puji; Rudiyansyah (Universitas Andalas, 2024)
Gitaan (Willughbeia coriacea Wall.) is an endemic plant that grows wild in the forests of Kalimantan. Traditionally, parts of this plant have been applied for fork-lore medication in Dayak tribe. However, scarce information both for secondary metabolites and biological activities of this plant has been reported, especially for flavonoids. This research was conducted to determine structure of flavonoid from ethyl acetate fraction of gitaan roots by spectroscopy analysis. The ethyl acetate fraction was purified by several chromatography techiques in order to isolate compound 1. On the basis of NMR analysis including DART-HRMS data and comparison with literature, an isoflavonoid obtained from the ethyl acetate fraction of gitaan roots is formononetin.